ANALISIS PERHITUNGAN BIAYA HARGA POKOK PRODUKSI PADA UMKM HEALTHY FOOD PURWOKERTO - Faizal Rizky Yuttama; Iin Dyah Indrawati (Ekomania, 2024)
The total costs associated with a product, including raw material costs, direct labor costs, and manufacturing overhead, are consolidated to form the cost of goods manufactured (COGM), which serves as a basis for business owners to determine the selling price of products offered to consumers. This study aims to assist the micro, small, and medium enterprise (MSME) Healthy Food in calculating its total production costs. The data in this research were analyzed using a descriptive quantitative approach. In other words, the data analysis provides recommendations to create a more efficient COGM. A single production sample of 30 pieces of Healthy Food products was completed in one day. The study highlights the critical role of employing the COGM method in calculating production costs for MSMEs to set competitive selling prices. By accurately understanding production costs, Healthy Food MSME can establish appropriate pricing, enhance profitability, and make strategic decisions in business management.